Sex differences in loneliness, social isolation, and their impact on psychiatric symptoms and cognitive functioning in schizophrenia - Jinghui Chi; Nannan Liu; Tian Tian; Qiaona Jiang; Chenghao Lu; Yanzhe Li; Xiaofei Zhang; Yanyan Ma; Lili Wang; Shen Li (BMC Psychiatry)
Abstract Background Social isolation and loneliness, objective and subjective features of dysfunctional social relationships, are more prevalent in patients with schizophrenia (SCZ) than in the general population. This study aimed to explore sex differences in loneliness and social isolation among Chinese chronic SCZ patients, and to investigate their relationships with psychiatric symptoms and cognitive functioning. Methods A total of 323 SCZ patients, comprising 136 males and 187 females, were recruited. Psychopathology, cognitive functioning, loneliness, social isolation were assessed using the Positive and Negative Syndrome Scale (PANSS), the Repeated Battery for Assessment of Neuropsychological Status (RBANS), the UCLA (University of California, Los Angeles) Loneliness Scale (Version 3) and the Social Isolation Index (ISI). Multiple linear regression models were conducted to test the independent, relative, and synergistic efects of loneliness and social isolation on psychiatric symptoms and cognitive performance for male and female patients separately. Results Male patients exhibited higher UCLA loneliness scale scores and social isolation scores compared to female patients (p s < 0.05). In male patients, both loneliness and social isolation significantly predicted PANSS total scores (p s < 0.01), negative subscale scores (p s < 0.05) and general psychopathology subscale scores (p s < 0.05). For female patients, loneliness (not social isolation) significantly predicted immediate memory (p < 0.001), language (p = 0.013), delayed memory (p = 0.017), and RBANS total scores (p = 0.002). Further examination of loneliness components in female patients revealed that personal feelings of isolation were negatively associated with language (r = -0.21, p = 0.001) and a negative correlation exists between lack of collective connectedness and delayed memory (r = -0.19, p = 0.048). Conclusion Loneliness and social isolation are more pronounced in male SCZ patients than in female patients. Both loneliness and social isolation are positively related to psychiatric symptoms in male patients, while loneliness is negatively associated with cognitive functioning in female patients.